2014
DOI: 10.3176/oil.2014.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Oil Shale Ash Based Stone Formation – Hydration, Hardening Dynamics and Phase Transformations

Abstract: Combustion of low calorific fuel-oil shale-in industrial-scale pulverized firing and circulating fluidized bed combustion boilers produces large amounts of ash. Estonian oil shale ash is characterized by a high content of free CaO as compared to those listed in the European Standard EN 450. The main alternatives to oil shale ash utilization include its use as a lime replacement in mineral binders or as a constituent of Portland cement. The pulverized firing ash formed at 1400 °C has been effectively used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
3
16
0
Order By: Relevance
“…Transformation of hydrated Ca-rich OS ash and its initial self-cementation are well characterised in laboratory-scale experiments (Liira et al, 2009;Raado et al, 2014;Uibu et al, 2016) but ash material transformations and long-term stability under real environmental conditions have been poorly studied. Similarly, the in situ studies of mechanical and mineralogical stability of waste depositories (Nguyen et al, 2015;Yvon et al, 2006) have focused on short-term changes, those occurring after only a few years.…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of hydrated Ca-rich OS ash and its initial self-cementation are well characterised in laboratory-scale experiments (Liira et al, 2009;Raado et al, 2014;Uibu et al, 2016) but ash material transformations and long-term stability under real environmental conditions have been poorly studied. Similarly, the in situ studies of mechanical and mineralogical stability of waste depositories (Nguyen et al, 2015;Yvon et al, 2006) have focused on short-term changes, those occurring after only a few years.…”
Section: Introductionmentioning
confidence: 99%
“…XRD analysis (Table 1) indicated that compared to the PF OSA fractions (1A EF1, 1A CA), the CFB OSA (8A mix , 8A EF1) contained more calcite (CaCO 3 ) and less free lime (CaO free ). Due to the relatively high amorphous phase content in PF OSA [38] the results of the qXRD analysis do not agree with those of standard chemical analysis of CaO and CaCO 3 contents (Table 1). In CFB OSA samples, silica compounds were mainly represented by quartz (SiO 2 ) and orthoclase type K-feldspar (KAlSiO 3 ), while the PF OSA samples contained noticeably more secondary silicates -belite (Ca 2 SiO 4 ) and merwinite (Ca 3 Mg(SiO 4 ) 2 ).…”
Section: Main Characteristics Of Osa and Bdmentioning
confidence: 80%
“…Lie, C. Rang. They also modify a theory about atmosphere influence to the thermal processing of shale [18,19].…”
Section: Discussionmentioning
confidence: 99%